Oxidative stress and lung pathology following geogenic dust exposure. Issue 10 (29th February 2016) - Leetham, M.; DeWitt, J.; Buck, B.; Goossens, D.; Teng, Y.; Pollard, J.; McLaurin, B.; Gerads, R.; Keil, D.
ABSTRACT: This study was designed to evaluate markers of systemic oxidative stress and lung histopathology following subacute exposure to geogenic dust with varying heavy metal content collected from a natural setting prone to wind erosion and used heavily for off‐road vehicle recreation. Adult female B6C3F1 mice were exposed to several concentrations of dust collected from seven different types of surfaces at the Nellis Dunes Recreation Area in Clark County, Nevada, designated here as CBN 1‐7. Dust representing each of the seven surface types, with an average median diameter of 4.2 μm, was selected and administered via oropharyngeal aspiration to mice at concentrations from 0.01 to 100 mg of dust kg –1 of body weight. Exposures were given four times spaced a week apart over a 28 day period to mimic a month of weekend exposures. Lung pathology was evaluated while plasma markers of oxidative stress included levels of reactive oxygen and nitrogen species, superoxide dismutase, total antioxidant capacity and total glutathione. Overall, results of these assays to evaluate markers of oxidative stress indicate that no single CBN surface type was able to consistently induce markers of systemic oxidative stress at a particular dose or in a dose–response manner. All surface types were able to induce some level of lung inflammation, typically at the highest exposure levels. These data suggest that dust from the Nellis Dunes Recreation Area may present a potential health risk, but additional studies are necessary to characterize the full extent of health risks to humans. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This study was designed to evaluate markers of systemic oxidative stress and lung histopathology following subacute exposure to geogenic dust with varying heavy metal content collected from a natural setting prone to wind erosion and used heavily for off‐road vehicle recreation.